Smart City Governance Strategies to Better Move Towards a Smart Urbanism - Azzari, Margherita; Garau, Chiara; Nesi, Paolo; Paolucci, Michela; Zamperlin, Paola (Computational Science and Its Applications - ICCSA 2018, 2018)
This paper intends to summarize the principal reached objectives of an ongoing project on smart cities governance called GHOST financed by MIUR (Italian Ministry of Education, Universities and Research), in order to provide an overview on how the smart governance analysis applied to smart urbanism has evolved in two particular case studies in Italy (Cagliari and Florence). Firstly, authors analyze the concept of ‘Smart City Governance’ (SCG), it is associated with a set of commonly accepted terminologies and not yet standardized even if nowadays academic attention to smart cities and their governance is growing rapidly. Secondly, this paper analyses the major aspects of smart city governance applied to case studies from: (i) the governance data acquisition approach with particular reference to tourism sector, and (ii) the adaptations of urban strategies (in general) and of these data acquisition in Florence and in Cagliari (in particular), due to the Km4city city dashboard, created and developed by the DISIT lab. The paper concludes by evaluating the emerged results of the case studies analysis, in order to find the necessary balance for urban synergies, and, consequently, to better move towards a smart urbanism.